A Study on Influencing Factors of Willingness to Use E-CNY Based on Logistic Model - Li, Yunfei; Wareewanich, Thitinant; Chankoson, Thitinan (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The development of mobile technology has facilitated the widespread adoption of digital currency worldwide. An important application of mobile technology is digital currency, which has gained global popularity due to its blockchain and peer-to-peer mobile payment mechanisms. The emergence of private digital currencies, such as Bitcoin, poses a challenge to the monetary policy of governments. To address this threat, many central banks are developing their own central bank digital currencies (CBDCs) with legal support. China’s CBDC, e-CNY (electronic China Yuan), is one of the most advanced examples of this innovation. However, the adoption and usage of e-CNY by residents is still limited and requires improvement. This paper aims to identify and analyze the factors that influence residents’ willingness to use e-CNY, based on a literature review and a logistic regression model. The results indicate that residents’ awareness, convenience, cost, promotional activities, and the involvement of relevant parties (merchants, commercial banks, payment institutions, and the People’s Bank of China (PBC)) significantly influence their willingness to use e-CNY. This paper presents implications and suggestions for promoting and implementing e-CNY in China.